Protection against Indonesian Women Workers - Putra, Septeryan Dwi Purnomo (Universitas Negeri Semarang, 2019)
Employment problems in Indonesia such as never discussed after the Indonesian government in which the essence of national development is the development of the Indonesian people as a whole and the development of Indonesian society entirely. Protection against the guarantee of the security of all forms of violence whether physical or psychological, abuse, rape, torture, persecution, murder, expulsion, or in other words to provide protection against acts of arbitrariness of the persons. Some reasons why we put our work abroad, in addition to being one alternative to solve the problem of unemployment. It can also be used to increase foreign exchange earnings for the country.